Enhancing traffic capacity of multilayer networks with two logical layers by link deletion - Ma, Jinlong; Sun, Zhichao; Zhang, Yongqiang (IET control theory & applications, 2022)
Improving the traffic capacity of multilayer networks has been the subject of extensive interest and research. This paper proposes an effective strategy to improve traffic capacity of three‐layer networks via the process of removing links linking to nodes with large degrees. In order to improve the traffic capacity, two different link deletion rules are proposed to remove a portion of logical layer links without the change of physical layer topology structure. It is found that the proposed strategy can improve traffic capacity; furthermore, the link deletion rule that two logical layers delete the same number of links at the same time is better than the link deletion rule that only the links of one logical layer are deleted. This work contributes to the design and optimization of realistic multilayer networks. This paper proposes an effective strategy to improve traffic capacity of three‐layer networks via the process of removing links linking to nodes with large degrees. Under the premise that the structure of physical layer in three‐layer networks does not change, some logical layer links between the nodes with large degrees are removed to improve the traffic capacity, and two different link deletion rules are proposed.